Executive compensation, company performance, size and managerial control of public listed companies in Sarawak. - Bujang, Fatimah; Jusoff, Kamaruzaman; Banchit, Azilawati; Kamri, Thalany; Abang Naim, Dayang Milianna; Aba Ibrahim, Muliati; Abu Samahh, Aizimah (2011)
In corporate governance, the executive compensation appears to be the controversial issue among the stakeholders as well as the shareholders. This study is to find the relationship between executive compensation and the company performance, size and managerial controls in Sarawak. Using all 22 public listed companies in Sarawak, data in annual reports from 2004 to 2006 were gathered. The result showed that there is a weak positive relationship between executive compensation with the company performance (ROS) and size (sales), while no relationship was found between the executive compensation and the managerial control.